Effect of Grape Seed Extract Powder on Shelf Life of Superchilled Chicken Sausage - Dhagare, L. G.; Rathod, K. S.; Badhe, S.R.; Patil., P. S. (Journal of Meat Science, 2022)
The shelf life of chicken sausage was assessed by incorporating 0.25% grape seed extract powder (GSEP) under superchilling storage and compared with chicken sausages incorporated with BHT and Control (without any antioxidant). The moisture, pH, peroxide value in GSEP treated samples increased significantly (P<0.05) throughout storage period TBARS, tyrosine and peroxide levels were marginally lower in GSEP treated chicken sausages than in control and BHT treated products. Over the course of the storage period, the protein, moisture and fat content of all the treated samples dropped gradually. In addition, GSEP treated chicken sausages had the lowest total plate count and psychrophilic count, followed by BHT. The study revealed that with the combined effect of superchilling and incorporation of 0.25% GSEP, the chicken sausage could be stored conveniently under aerobic conditions up to 35 days.